CDKN2A loss and PIK3CA mutation in myoepithelial‐like metaplastic breast cancer. Issue 3 (28th May 2018) - Bartels, Stephan; van Luttikhuizen, Jana Lisa; Christgen, Matthias; Mägel, Lavinia; Luft, Angelina; Hänzelmann, Sonja; Lehmann, Ulrich; Schlegelberger, Brigitte; Leo, Fabian; Steinemann, Doris; Kreipe, Hans
Abstract: Metaplastic breast carcinoma comprises a heterogeneous group of tumours with poorly understood pathogenesis. A subset of metaplastic breast cancers show myoepithelial differentiation and constitute a morphological spectrum with ill‐defined borders from fibromatosis‐like spindle cell carcinoma to myoepithelial carcinoma. In a series of 34 metaplastic breast cancers with spindle cell and myoepithelial differentiation, we found recurrent genetic aberrations, which set them apart from other metaplastic breast cancers and suggest a unique pathogenesis. The majority of cases (28 of 34 patients; 82.4%) showed distinct chromosomal loss in the 9p21.3 region, including CDKN2A and CDKN2B . Biallelic loss of the CDKN2A / B region was found in 50% of deleted cases. Expression of the cyclin‐dependent kinase inhibitor CDKN2A (p16) was missing in all samples affected by 9p21.3 loss. Other genomic alterations frequently occurring in triple‐negative and metaplastic breast cancer were absent or found in only a minority of cases. Gains of whole chromosome 5 and chromosomal region 5p were observed in nine cases, and were associated with recurrences ( p < 0.001). In 64.3% of cases, 9p21.3 loss was accompanied by concurrent PIK3CA mutation. Both genomic abnormalities were also detectable in adenomyoepitheliomas (4/12), which are considered to represent the precursor lesion of myoepithelial metaplastic breast cancer. In adenomyoepithelioma, PIK3CA mutation was present in both luminal epithelial and myoepithelial cells, whereas p16 loss was found only in the latter. We conclude that 9p21.3 ( CDKN2A ) loss and PIK3CA mutation characterize a subgroup of metaplastic breast cancers with myoepithelial and spindle cell differentiation. Myoepithelial cells in adenomyoepithelioma may show identical aberrations. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.